2023
DOI: 10.1101/2023.11.14.566895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

tRNA modification enzyme-dependent redox homeostasis regulates synapse formation and memory

Kimberly R. Madhwani,
Shanzeh Sayied,
Carlson H. Ogata
et al.

Abstract: Post-transcriptional modification of RNA regulates gene expression at multiple levels. ALKBH8 is a tRNA modifying enzyme that methylates wobble uridines in specific tRNAs to modulate translation. Through methylation of tRNA-selenocysteine, ALKBH8 promotes selenoprotein synthesis and regulates redox homeostasis. Pathogenic variants in ALKBH8 have been linked to intellectual disability disorders in the human population, but the role of ALKBH8 in the nervous system is unknown. Throughin vivostudies inDrosophila, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…From these analyses, we identified the tRNA-methyltransferase AlkBH8 as a potential novel therapeutic target in CRC, as high AlkBH8 expression correlates with decreased overall survival in CRC patients (Figure 5A-B). AlkBH8 has been extensively reported to regulate the selenoproteome via methylation of tRNA-selenocysteine, with AlkBH8 knockdown and knockout models demonstrating a decreased ability to translate selenoproteins [54][55][56][57][58][59][60][61] . We observed that AlkBH8 expression is significantly increased in tumor tissue as compared to normal controls (Figure 5C), and that patients with early-onset CRC have increased expression of AlkBH8 as compared to all other age groups (Figure 5D).…”
Section: Investigating the Selenoproteome As A Therapeutic Target In ...mentioning
confidence: 99%
“…From these analyses, we identified the tRNA-methyltransferase AlkBH8 as a potential novel therapeutic target in CRC, as high AlkBH8 expression correlates with decreased overall survival in CRC patients (Figure 5A-B). AlkBH8 has been extensively reported to regulate the selenoproteome via methylation of tRNA-selenocysteine, with AlkBH8 knockdown and knockout models demonstrating a decreased ability to translate selenoproteins [54][55][56][57][58][59][60][61] . We observed that AlkBH8 expression is significantly increased in tumor tissue as compared to normal controls (Figure 5C), and that patients with early-onset CRC have increased expression of AlkBH8 as compared to all other age groups (Figure 5D).…”
Section: Investigating the Selenoproteome As A Therapeutic Target In ...mentioning
confidence: 99%